Ganti Rugi Penadah Sawit Hasil Curian Terhadap Petani Kelapa Sawit Perspektif Wahbah Az-Zuhaili (Studi Kasus Desa Sei Rakyat Kecamatan Panai Tengah Kabupaten Labuhanbatu) - Ibnu Qudama; Fatimah Zahara (Dinasti Review Publisher, 2024)
The importance of this research can be seen from the perspective of Wahbah Az-Zuhaili who emphasizes justice and moral values ??in Islamic law. By integrating Az-Zuhaili's views as study material, this research can provide a holistic evaluation of oil palm harvesting practices. A qualitative approach in this research was used to gain an in-depth understanding of the practice of handling stolen palm oil and its impact on farmers in Sei Rakyat Village. By applying a qualitative approach to explore the practice of handling stolen palm oil and its impact on farmers in Sei Rakyat Village. Through in-depth interviews, participant observation, and document analysis, this research succeeded in providing an in-depth understanding of this phenomenon. The principle of compensation is that if you damage other people's property and the like, whether it is destroying objects, stealing or confiscating property from someone, you must return it with the same or similar item as long as the item is still there. If the item is difficult to find, you can replace it in the form of money in accordance with nominal loss figure. Wahbah Az-Zuhaili emphasized the need to resolve compensation actions through mutual consent and agreement between the parties involved, referring to the principles of consensual commerce. The results of this research state that oil palm farmers should compensate for losses in a similar form to the compensation requested by oil palm farmers.